2022
DOI: 10.1002/mde.3752
|View full text |Cite
|
Sign up to set email alerts
|

Managing supply chain with green and non‐green products: Channel coordination and information asymmetry

Abstract: We examine a supply chain where a supplier produces partial substitutable green and non-green products and sell them in a common market through a buyer. We analyse four scenarios: wholesale price and linear two-part tariff contracts under full and incomplete information about the buyer's unit cost. Our result demonstrates that the value of information and trade cutoff points both increase with consumer greening sensitivity and decrease with greening investment. When green product market share exceeds a certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The findings suggested that the manufacturer will invest more to enhance the product's greenness after blockchain adoption, which also benefits the retailer when the improvement of consumers' green sensitivity levels derived from blockchain is relatively high. In a global supply chain, Biswas et al (2023) proposed a game theory model to analyze the implications between traceability and sustainability for blockchain adoption. They found that high levels of distrust of product quality prevent firms from adopting blockchain technology.…”
Section: Blockchain Technology Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings suggested that the manufacturer will invest more to enhance the product's greenness after blockchain adoption, which also benefits the retailer when the improvement of consumers' green sensitivity levels derived from blockchain is relatively high. In a global supply chain, Biswas et al (2023) proposed a game theory model to analyze the implications between traceability and sustainability for blockchain adoption. They found that high levels of distrust of product quality prevent firms from adopting blockchain technology.…”
Section: Blockchain Technology Adoptionmentioning
confidence: 99%
“…The functional quality obtained by consumers from green products is italicαV, where α( >1) is the parameter indicating the difference in functional quality between the two products (Hong et al, 2018, 2019). Besides, the environmental utility obtained by consumers from green products is assumed to be a linear function (i.e., italicke), where e represents the green degree of the green product and k represents the environmental awareness level of consumers for green technologies (Chen, 2001; Hu et al, 2023; Singh et al, 2023; Xu, Zhang, et al, 2023; Zhang et al, 2017). The larger the green degree of products, the higher the environmental utility obtained by consumers.…”
Section: Model Developmentmentioning
confidence: 99%
“…Several studies have examined the competition between green and non‐green products (Shen et al, 2020; Singh et al, 2023; Yenipazarli & Vakharia, 2015). Jamali and Rasti‐Barzoki (2018) analyzed pricing strategies employed within two dual‐channel supply chains for both green and non‐green products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The increasing attention to environmental protection issues around the world has also promoted academic research on the green supply chain (Heydari et al, 2023; Shi et al, 2022; Taleizadeh et al, 2020; Zhang et al, 2022). For example, several scholars have compared the green supply chain with the conventional supply chain under a sustainable development context (Singh et al, 2022; Wang & Song, 2020; Zhang et al, 2015). Some scholars have focused on low‐carbon supply chain, investigating the carbon emission reduction in the production and operations process of upstream and downstream enterprises (Alizadeh‐Basban & Taleizadeh, 2020; Taleizadeh et al, 2021; Taleizadeh, Alizadeh‐Basban, & Sarker, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%